2002
DOI: 10.1080/096382301200041542
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorder, primary care counselling and therapeutic effectiveness

Abstract: An evaluation of a primary care counselling service was conducted. Measures completed by clients were the CORE questionnaire (assessing subjective well-being, symptoms, functioning and risk) and the DIS(BI) (Swartz et al., 1990) identifying cluster B personality disorders. Counsellors' written accounts of the benefits gained in therapy by their clients were also collected. At assessment, it was found that mean scores on the CORE questionnaire suggested the client group was experiencing similar levels of distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…There have been few studies to date that have investigated PD in primary care medical and mental health participants. This study focused on a sample of the latter group referred for psychological treatment, confirming previous reports of the high frequency of PD presentations to non-specialist services (Howey and Ormrod, 2002). Rates of PD were also similar to those of 30-60% comorbidity in larger US samples (Brown and Barlow, 1992;Shea, Widiger and Klein, 1992).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There have been few studies to date that have investigated PD in primary care medical and mental health participants. This study focused on a sample of the latter group referred for psychological treatment, confirming previous reports of the high frequency of PD presentations to non-specialist services (Howey and Ormrod, 2002). Rates of PD were also similar to those of 30-60% comorbidity in larger US samples (Brown and Barlow, 1992;Shea, Widiger and Klein, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…In primary health care, Moran found 24% of patients met criteria for PD according to informant interviews (Moran, Jenkins, Tylee, Blizard and Mann, 2000). Moreover, Howey and Ormrod reported 50% of primary care counselling patients met PD criteria on a self-report measure (Howey and Ormrod, 2002), whilst a report from the UK Department of Health for 2000-2001 noted 76,300 referrals to Clinical Psychology Departments in England (DoH, 2001). These figures indicate that the vast majority of people with PD will not be seen by specialist PD services.…”
Section: Introductionmentioning
confidence: 99%
“…These included enhancement of interpersonal functioning and teaching self-monitoring to allow early selfintervention during relapses (Miklowitz & Scott, 2009). Such processes have also been implicated in interpersonal therapy (IPT) (Lipsitz & Markowitz, 2013) and can be seen to be present in other therapies such as CBT (Livesley, 2007;Steever, 1999), MBT (Epstein et al, 2008) and counselling (Howey & Ormrod, 2002). It was particularly noteworthy that effective therapies shared a number of common characteristics with regards to how the model of therapy was shared with the patient, how the therapy was delivered and the structuring of treatment (Miklowitz & Scott, 2009).…”
Section: Shared Mechanisms In Psychotherapymentioning
confidence: 99%
“…Evidence from RCTs has, however, been criticized because the level of control required in the design of RCTs makes them unrepresentative of everyday practice (Hemmings, 2000;Mellor-Clark, 2000b;2000c;Howey and Ormrod, 2002). In this respect Hemmings (2000) draws a distinction between efficacy and effectiveness research.…”
mentioning
confidence: 99%
“…Hemmings (2000), who lists further limitations of RCTs for evaluating counselling, reviewed effectiveness studies of counselling as delivered in naturalistic, everyday practice and found improved psychological well-being measured across a range of measures. A number of studies evaluating counselling in primary care contexts have reported improvements in patient well-being (Baker et al, 1998;Nettleton et al, 2000;Howey and Ormrod, 2002), often maintained in the long term (two years' follow-up) (Gordon and Wedge, 1998;Baker et al, 2002).…”
mentioning
confidence: 99%